Analisis Curahan Waktu Kerja Istri Nelayan di Dalam dan di Luar Sektor Perikanan - Siti Nazariani; Khairul Saleh; Endang Sari Simanullang (Universitas Medan Area, 2020)
This thesis purpose to analyze expression total of time working wife inside and outside fishery sector, the factor’s influence time working expression fisherman’s wife inside fishery sector, the factor’s influence time working expression fisherman’s wife outside fishery sector in the Belawan Bahagia district Medan Belawan subdistrict. Method data analysis that used is multiple linear regression analysis. Riset effect showed that the fisherman's wife working hours outside the fisheries sector is greater than devote time work in with the fisherman's wife in the fisheries sector. The factors that influence the working hours in the fisherman's wife in the fisheries sector in the activities peeled shrimp significant are age, number of burden, pay quantity, long working experience. Shellfish peeling activities significant are age, number of burden, pay quantity, long working experience, long education. Shrimp Selling activities significant are age, number of burden, pay quantity, long working experience, long education. Fish drying activities significant are age, number of burden, pay quantity, long working experience, long education. The factors that influence the fisherman's wife working hours outside the fisheries sector significant washing activities are age, number of burden, pay quantity.